Ascorbic acid promoted sulfamethoxazole degradation in MIL-88B(Fe)/H2O2 Fenton-like system. Issue 1 (February 2023) - Han, Xiaolin; Wang, Nannan; Zhang, Wei; Liu, Xiaodong; Yu, Qi; Lei, Juying; Zhou, Lei; Xiu, Guangli
Abstract: In this work, the presence of ascorbic acid (AsA) in MIL-88B(Fe)/ H2 O2 system was demonstrated to significantly increase the sulfamethoxazole (SMX) degradation efficiency. The SMX degradation rate in AsA/MIL-88B(Fe)/ H2 O2 system was 0.177 L/(mg∙min), which was 60 times that of the MIL-88B(Fe)/ H2 O2 system. Moreover, the study shows that AsA not only promotes SMX degradation in Fenton-like systems but also expands its pH application range. The effect of coexisting anions on the catalytic performance of the AsA/MIL-88B(Fe)/ H2 O2 system was also investigated. Then, reactive species were detected via quenching experiments, which indicated OH as the dominant free radical contributing to SMX degradation. Meanwhile, ESR determinations confirmed the existence of OH and O2 − in AsA/MIL-88B(Fe)/ H2 O2 system. The high activity of the AsA/MIL-88B(Fe)/ H2 O2 system was attributed to the effective surface Fe(III)/Fe(II) cycle promoted by AsA, and a possible mechanism of the AsA/MIL-88B(Fe)/ H2 O2 system is proposed. The possible pathways for SMX and AsA degradation in the AsA/MIL-88B(Fe)/ H2 O2 system are proposed based on the identified intermediates and the ecotoxicity analysis was conducted by ECOSAR. Finally, experimental results using the actual surface water and groundwater revealed the excellent availability of AsA/MIL-88B(Fe)/H2 O2 system in remediating SMX contaminated water. This study presents a novel, efficient Fenton-like system using AsA and iron-based metal-organic frameworks for sulfonamide removal from water. Highlights: ASA significantly increased the SMX degradation efficiency. ASA expanded the pH application range in Fenton-like process. OH was the dominant free radical contributed to the SMX degradation. The surface Fe(III)/Fe(II) cycle on MIL-88B(Fe) was promoted by ASA. The notable reusability and stability of MIL-88B(Fe) was revealed.